Sensing mode coupling analysis for dual-mass MEMS gyroscope and bandwidth expansion within wide-temperature range. (1st January 2018) - Cao, Huiliang; Li, Hongsheng; Shao, Xingling; Liu, Zhiyu; Kou, Zhiwei; Shan, Yanhu; Shi, Yunbo; Shen, Chong; Liu, Jun
Highlights: The real working mode of dual-mass gyroscope sense coupling mode is analyzed. A high effective test method is proposed based on the sense mode feedback combs. The restrict element of mechanical structure bandwidth is calculated and tested. The proportional integral phase lead controller for sense close loop is proposed. The bandwidth under wide-temperature are tested, the results verify the theory analysis. Abstract: This paper presents the bandwidth expanding method with wide-temperature range for sense mode coupling dual-mass MEMS gyro. The real sensing mode of the gyroscope is analyzed to be the superposition of in-phase and anti-phase sensing modes. The mechanical sensitivity and bandwidth of the gyroscope structure are conflicted with each other and both governed by the frequency difference between sensing and drive modes (min {Δω1, Δω2}). The sensing mode force rebalancing combs stimulation method (FRCSM) is presented to simulate the Coriolis force, and based on this method, the gyro's dynamic characteristics are tested. The sensing closed- loop controller is achieved by operational amplifier based on phase lead method, which enable the magnitude margin and phase margin of the system to reach 7.21 dB and 34.6° respectively, and the closed-loop system also expands gyro bandwidth from 13 Hz (sensing open-loop) to 102 Hz (sensing closed-loop). What's more, the turntable test results show that the sensing closed-loop works stably in wide-temperature range (from −40 °C to 60 °C) and the bandwidth values are 107 Hz @−40 °C and 97 Hz @60 °C. The results indicate that the higher temperature causes lower bandwidth, and verify the simulation results are 103 Hz @−40 °C and 98.2 Hz @60 °C. The new bottleneck of the closed loop bandwidth is the valley generated by conjugate zeros, which is formed by superposition of sensing modes.